SOME FİSH SPECİES SHOWİNG COMMENSALİSM TRAİTS WİTH LONG-SPİNED SEA URCHİN (Diadema setosum Leske, 1778) İN GULF OF ANTALYA - Ferhat ÇAĞILTAY; Mehmet Gökoğlu; Ramazan Yılmaz; Alper Yıldız (Indonesian Fisheries Research Journal, 2022)
This research was carried out with a rocky (Cliffs: 36°53'3.13"N; 30°41'49.78"E) stony and gravelly bottom (Konyaaltı beach: 36°53'0.07"N; 30°4043.36"E) in two different regions of Gulf of Antalya. This study was intended to determine the fish species that use the long-spined sea urchin (Diadema setosum Leske, 1778) as a shelter. In the study, the fish that use the sea urchin in the rocky area as a sheltered area Chromis Chromis, Cheilodipterus novemstriatus, Thalassoma pavo, Coris julis, Tripterygion melon rum, Gobius bucchichi. Of these species, only C. novemstriatus is exotic. Others are native species of the Mediterranean. C. Chromis juveniles were the densest among the sea urchin spines in the rocky region, while C. novemstriatus formed the second crowded species. In the study carried out in the second area, which has a stony and gravelly bottom structure, fish species that use sea urchins as shelter are C. novemstriatus, Siganus rivulatus, Apogonichthyoides pharaonic, Pteragogus pelycus, Parupeneus forsskali, Pterois miles, Sargocentron rubrum, Epinephelus aeneus and C. julis. Of these species, only E. aeneus and C. julis were determined to be native species of the Mediterranean. All other species are Red Sea species, with Rabbitfish (S. rivulatus) fry as the densest species, C. novemstriatus in the second place and A. pharaonis in the third place are. It was determined that adult and juvenile individuals of C. novemstriatus, A. pharaonic and P. pelycus used sea urchins as shelter, and only juveniles of other species. In addition, among the sea urchin spines, most of the C. novemstriatus, and A. pharaonis individuals were found to carry eggs in their mouths. According to the findings obtained in this study, it can be said that the long-spined sea urchin, which increases its population rapidly in the Mediterranean, also contributes to the increase in their population in the Mediterranean by creating a shelter for some fish species of Red Sea origin that cannot be economically evaluated and invaded.